One year of 222Rn concentration at a typical rural site in South India - K Charan Kumar (Wolters Kluwer Medknow Publications, 2021)
The simultaneous measurements of atmospheric radon, ambient gamma radiations dose, and relevant meteorological parameters were carried out at the National Atmospheric Research Laboratory (NARL), Gadanki, India (13.459° N, 79.175° E) during June 2013–May 2014 are analyzed and presented. The results show that radon strongly correlates with temperature, relative humidity, and a weak correlation with air pressure, ambient gamma dose during fair weather days. Radon's well-defined monthly variability is observed, with the highest during winter and lowest during monsoon season. The fast Fourier transform analysis revealed a hidden memory in variations in radon activity with prominent peaks at 24 h and 12 h, indicating the influence of atmospheric stability on the abundance of radon in air. About 99% of radon activity lies below 70 Bq/m3 with a mean value of 11.81 ± 4.83 Bq/m3, and about 99% ambient gamma dose levels range from 140 to 240 nSv/h at NARL with a mean value of 192.17 ± 17.43 nSv/h. The ambient gamma dose levels are well within limits prescribed by the UNSCEAR.